Analysis of Cost Stickiness, Customer Concentration, and Operational Cost Efficiency on Financial Risks of Manufacturing Companies in the Indonesian Stock Exchange (BEI) for the 2022-2024 Period - Rosaidina Syafira; Hwihanus (Escalate : Economics and Business Journal, 2026)
Financial risk is a critical issue for manufacturing companies due to operational complexity, high capital intensity, and economic dynamics in the 2022–2024 period, which increase pressure on companies' financial performance. This study aims to analyze the financial risk conditions of manufacturing companies listed on the Indonesia Stock Exchange using the Altman Z-Score (Emerging Market Score) model. The study employed a quantitative approach with descriptive methods. The study population comprised all manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period, while the sample consisted of companies with complete financial reports during the observation period. The research instrument consisted of financial report data analyzed using the Altman Z-Score through descriptive analysis. The results showed that the average Z-score value increased from 2.18 in 2022 to 2.47 in 2024, the proportion of companies in the safe zone increased, while the proportion of companies in the distress zone decreased. Furthermore, the pharmaceutical and healthcare, automotive, and chemical and petrochemical subsectors had better risk profiles than the textile and footwear subsectors. This study concludes that the financial risk conditions of manufacturing companies have improved, but in aggregate are still in the grey zone, so continuous risk monitoring is needed to support decision-making by management, investors, creditors, and regulators